2010
DOI: 10.1111/j.1365-2958.2010.07239.x
|View full text |Cite
|
Sign up to set email alerts
|

The mycobacteriophage Ms6 encodes a chaperone‐like protein involved in the endolysin delivery to the peptidoglycan

Abstract: SummaryLike most double-stranded (ds) DNA phages, mycobacteriophage Ms6 uses the holin-endolysin system to achieve lysis of its host. In addition to endolysin (lysA) and holin (hol ) genes, Ms6 encodes three accessory lysis proteins. In this study we investigated the lysis function of Gp1, which is encoded by the gp1 gene that lies immediately upstream of lysA. Escherichia coli lysis was observed after coexpression of LysA and Gp1 in the absence of Ms6 holin. Gp1 does not belong to the holin class of proteins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
101
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(104 citation statements)
references
References 42 publications
3
101
0
Order By: Relevance
“…We propose that the second of these smaller genes (Bongo gp37, PegLeg gp37, and Rey gp42) is the holin, with each having two predicted transmembrane domains, although they are not related at the sequence level to any other mycobacteriophage proteins. The first small protein (e.g., Bongo gp36, 78 amino acids) contains an N-terminal predicted transmembrane domain, and its role is unclear, although it could perform a chaperone-like role in lysis, as proposed for gp1 of phage Ms6 (38). The lysin A proteins have domain structures corresponding to organization A (Org-A) (39), although the only other similar mycobacteriophage lysin is that encoded by the singleton phage Patience (gp41; 36% amino acid identity).…”
Section: Resultsmentioning
confidence: 99%
“…We propose that the second of these smaller genes (Bongo gp37, PegLeg gp37, and Rey gp42) is the holin, with each having two predicted transmembrane domains, although they are not related at the sequence level to any other mycobacteriophage proteins. The first small protein (e.g., Bongo gp36, 78 amino acids) contains an N-terminal predicted transmembrane domain, and its role is unclear, although it could perform a chaperone-like role in lysis, as proposed for gp1 of phage Ms6 (38). The lysin A proteins have domain structures corresponding to organization A (Org-A) (39), although the only other similar mycobacteriophage lysin is that encoded by the singleton phage Patience (gp41; 36% amino acid identity).…”
Section: Resultsmentioning
confidence: 99%
“…1A) (12). Recently, we have reported that export of the Ms6 endolysin (LysA) is holin independent and that LysA translocation across the cytoplasmic membrane is assisted by Gp1, a chaperone-like protein, encoded by the first gene of the Ms6 lysis cassette (2). These data, together with the absence of a lysis phenotype when Gp4 was coexpressed in E. coli with Ms6 endolysin (4), even when both proteins were shown to be expressed at detectable levels (M. J. Catalão, unpublished data), led us to reanalyze the amino acid sequence of Ms6 Gp4.…”
Section: Resultsmentioning
confidence: 99%
“…Construction of Ms6 mutants was performed using bacteriophage recombineering of electroporated DNA (BRED) in M. smegmatis. Recombineering substrates and BRED strategy were done as described previously (2,19). Briefly, for deletion of the Ms6 gp4, gp5, or gp4 and gp5 genes (yielding Ms6 ⌬gp4 , Ms6 ⌬gp5 , or Ms6 ⌬gp4 gp5 , respectively), 100-bp oligonucleotides, Pr⌬gp4, Pr⌬gp5, or Pr⌬gp4gp5, that have 50 bp of homology upstream and downstream of the region to be deleted, were extended by PCR using two 75-bp extender primers, PrExt⌬gp4fwd/PrExt⌬gp4rv, PrExt⌬gp5fwd/ PrExt⌬gp5rv, or PrExt⌬gp4fwd/PrExt⌬gp5rv, respectively, which have 25 bp of homology to the ends of the 100-mer and add an additional 50 bp of homology on either end.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Holins allow the endolysins to gain access to the cell wall, where they exert their actions by cleaving various bonds in the peptidoglycan polymer, depending on the type of endolysin (4,13). Genes encoding holin proteins and their target peptidoglycan hydrolases have been identified in a wide variety of Gram-negative and Gram-positive bacteria and their phages (1,(14)(15)(16)(17). While possible homologues are present in archaea (see holin families 1.E.3, 1.E.14, and 1.E.43 in TCDB), the functions of these proteins are not yet defined.…”
mentioning
confidence: 99%